The Anti-Inflammatory Drug Aspirin Does Not Protect Against Chemotherapy-Induced Memory Impairment by Paclitaxel in Mice - Chang, Aeson; Chung, Ni-Chun; Lawther, Adam J.; Ziegler, Alexandra I.; Shackleford, David M.; Sloan, Erica K.; Walker, Adam K. (Frontiers in Oncology, 2020)
Inflammation has been proposed to play a causal role in chemobrain which - if true - would represent an opportunity to repurpose existing anti-inflammatory drugs for the prevention and treatment of chemobrain. Here, we show that the chemoagent paclitaxel induces memory impairment and anhedonia in mice within 24 h of treatment cessation, but inflammation is not present until two weeks after treatment. We find no evidence of brain inflammation as measured by cytokine analysis at any time point. Furthermore, treating with aspirin to block inflammation did not affect paclitaxel-induced memory impairment. These findings suggest that inflammation may not be responsible for memory impairment induced by paclitaxel. These results contrast with recent findings of a causal role for inflammation in cancer-induced memory deficits in mice that were prevented by treatment with oral aspirin, suggesting that cognitive impairment in cancer patients undergoing treatment may arise from multiple convergent mechanisms.